2010
DOI: 10.1038/nature09387
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast differentiation factor RANKL controls development of progestin-driven mammary cancer

Abstract: Breast cancer is one of the most common cancers in humans and will on average affect up to one in eight women in their lifetime in the United States and Europe1. The Women’s Health Initiative and the Million Women Study have shown that hormone replacement therapy is associated with an increased risk of incident and fatal breast cancer2,3. In particular, synthetic progesterone derivatives (progestins) such as medroxyprogesterone acetate (MPA), used in millions of women for hormone replacement therapy and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
460
1
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 527 publications
(499 citation statements)
references
References 40 publications
24
460
1
14
Order By: Relevance
“…Recent studies show that MPA induces RANKL in DMBA-induced mammary tumors, which is consistent with a role for RANKL in the growth of progestin-dependent breast cancer [16,17]. Because MPA stimulates proliferation of BT-474 xenograft tumor cells, we examined whether RANKL might also be induced by MPA in BT-474 cells.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Recent studies show that MPA induces RANKL in DMBA-induced mammary tumors, which is consistent with a role for RANKL in the growth of progestin-dependent breast cancer [16,17]. Because MPA stimulates proliferation of BT-474 xenograft tumor cells, we examined whether RANKL might also be induced by MPA in BT-474 cells.…”
Section: Discussionsupporting
confidence: 73%
“…6c), suggesting that the flavonoid might reduce blood flow in BT-474 xenograft tumors. Immunohistochemical and ELISA Analysis of RANKL Recent studies in rodents showed that progestin induces expression of RANKL, and that RANKL may play a significant role in mammary tumor development [16,17]. Consequently, the effect of apigenin on RANKL expression in xenograft tumor-bearing mice was examined immunohistochemically.…”
Section: Immunohistochemical Analysis Of Angiogenic Factors/blood Vesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the P-dependent paracrine factor Wnt-4 has been reported to be important for proliferation in the normal mouse mammary gland [34]. Another P-regulated paracrine factor, receptor activator of nuclear factor kappa B ligand (RANKL), has been demonstrated to increase proliferation and mammary cancer development in the mouse and mediates P-induced proliferation in the normal human breast tissue [35][36][37]. However, whether or not Wnt-4 and RANKL contribute to breast cancer development or proliferation of breast cancer cells in vivo remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings from their group demonstrating an essential role for RANK in mammary gland development and progestin-driven mammary carcinogenesis [6,7], Penninger and collaborators initially set out to determine the impact of RANK signaling in multiple genetic models of mammary carcinogenesis, including: (1) mice bearing homozygous Brca1 fl/ fl alleles in a Trp53 fl/fl context (targeting the master oncosuppressor p53) and expressing the Cre recombinase under the control of the keratin 5 (Krt5) promoter, which is active in multiple epithelia; and (2) Brca1 fl/fl Trp53 fl/fl mice expressing the Cre C recombinase under the control of the whey acidic protein (Wap) promoter, which is specifically active in luminal and basal mammary epithelial cells independently of doxycycline and pregnancy. To this aim, they crossed the strains described here above with Tnfrsf11a fl/fl mice (in which the RANK-coding sequence is floxed), and monitored not only tumor incidence over time, but also biochemical and pathological parameters of developing neoplasms, including markers of DNA damage, proliferation rate and grade [3].…”
mentioning
confidence: 99%